A bibliometric analysis of the application of solar energy to the organic Rankine cycle. Issue 4 (April 2022) - Permana, Diki Ismail; Rusirawan, Dani; Farkas, Istvan
Abstract: Solar Thermal is one of many heat sources that support the organic Rankine cycle (ORC) system. The advantage of using solar thermal as a heat source when combined with the ORC system is that it can provide affordable energy supplies in remote areas and it is suitable in disaster territories. Growth in solar-ORC research is not only on a lab/workshop scale but also on an industrial scale. Most articles refer to methods and tools in the design process, combining heat and improvement of the cycle, working fluids selection, and case studies based on primary or secondary data. The paper reports the newest trends on the research of solar application on ORC using bibliometric analysis. The study of bibliometric using VOSviewer was recognized as a captivating method in the literature that allows examining the scientific progress of a particular topic. Moreover, a qualitative approach can be performed by analyzing the keywords contained in different documents to identify a circumstance that features the research trend and to understand future viewpoints. Abstract : Solar thermal, Improvement the cycle, VOSviewer, Qualitative approach.